Analysis of Risk Factors and Predictors of Endoscopic Findings in Patients with Gastrointestinal Disorders: A Single Center Observational Study at Sanjiwani General Hospital, Gianyar, Bali, Indonesia - Dwi Putri Anjani, I Gusti Agung; I Wayan Eka Saputra (HM Publisher, 2024)
Background: Gastrointestinal disorders are a common health problem in Indonesia. Endoscopy is an important procedure in diagnosing and managing this disorder. This study aims to analyze risk factors and predictors of endoscopic findings in patients with gastrointestinal disorders at regional hospitals in Bali. Methods: This research is an analytical observational study with a cross-sectional design. The research subjects were patients with gastrointestinal disorders who underwent endoscopy at regional hospitals in Bali during the period January 2022 to December 2023. Data was collected through medical records and interviews. Data analysis was carried out using the Chi-square test and logistic regression. Results: A total of 1074 patients were included in this study. The mean age of patients was 45.3 years (SD 15.2). The most common endoscopic finding was gastritis (35.2%), followed by gastric ulcer (15.8%) and esophagitis (12.4%). Risk factors that were significantly associated with endoscopic findings were age > 45 years (OR 1.78; 95% CI 1.23-2.57), male gender (OR 1.54; 95% CI 1.11- 2.14), history of smoking (OR 2.31; 95% CI 1.65-3.24), and history of use of non-steroidal anti-inflammatory drugs (NSAIDs) (OR 1.98; 95% CI 1.39-2.82). Conclusion: Age > 45 years, male gender, smoking history, and history of NSAID use are risk factors that are significantly associated with endoscopic findings in patients with gastrointestinal disorders at regional hospitals in Bali.